Need Help?

  • Notes
  • Comments & Questions

\( \begin{array}{l}{\text { Find the interval and radius of convergence of the power }} \\ {\text { series } : \sum \frac{(-1)^{n-1}}{\sqrt{n} \cdot 8^{n}}(x-2)^{3 n}}\end{array} \)

Apply Ratio test: \( u_{n}=\frac{(-1)^{n-1}}{\sqrt{n} \cdot 8^{n}} \cdot(x-2)^{3 n} \)

\( u_{n+1}=\frac{(-1)^{n+1-1}}{\sqrt{n+1} \cdot 8^{n+1}} \cdot (x-2)^{3(n+1)} =\frac{(-1)^{n}(x-2)^{3 n+3}}{\sqrt{n+1} \cdot 8^{n+1}} \)

\( \lim _{n \rightarrow \infty}\left|\frac{u_{n+1}}{n_{n}}\right|= \lim _{n \rightarrow \infty} |\frac{(-1)^{n}(x-2)^{3 n+3}}{\sqrt{n+1} \cdot 8^{n+1}}\cdot \frac{\sqrt{n} \cdot 8^{n}}{(-1)^{n-1} \cdot(x-2)^{3 n}} | \)

\( \lim _{n \rightarrow \infty}\left|\frac{u_{n}+1}{u_{n}}\right|=\lim _{n \rightarrow \infty} \frac{\sqrt{n} \cdot 8^{x}}{\sqrt{n+1} \cdot 8^{n+1}} \left|\frac{(x-2)^{3 n+3}}{(x-2)^{3n}}\right| =\lim _{n \rightarrow \infty} \frac{\sqrt{n}}{\sqrt{n+1}} \cdot\left|\frac{(x-2)^{3} }{8}\right| \)

\( \lim _{n \rightarrow \infty}\left|\frac{u_ n+1}{u _n}\right|=\frac{\left|(x-2)^{3}\right|}{8} \lim _{n \rightarrow \infty} \frac{\sqrt{n}}{\sqrt{n+1}} =\frac{\left|(x-2)^{3}\right|}{8} \lim _{n \rightarrow \infty} \sqrt\frac{n}{n(1+\frac{1}{n})}=\frac{|(x-2)^3|}{8} \lim _{x \rightarrow \infty} \frac{1}{\sqrt{1+\frac{1}{n}}} \)

\( \lim _{n \rightarrow \infty} {\left|\frac{u_ n+1}{u_{n}}\right|}=\frac{\left|(x-2)^{3}\right|}{8} (1)=\frac{\left|(x-2)^{3}\right|}{8} \)

\( \sum \frac{(-1)^{n-1}}{\sqrt{n} \cdot 8^{n}}(x-2)^{3 n} \) is \(A.C\) when \( \frac{\left|(x-2)^{3}\right|}{8}<1 \)

\( \sqrt[3]{\left|(x-2)^{3}\right|}<\sqrt[3]{8} \Rightarrow|x-2|<2 \)

\( -2<x-2<2 \)

\( 0<x<4 \)

Now we stady the Convergence at the bandries

\( (x=0 \text { and } x=4) \)

when \( x=0 \Rightarrow \sum \frac{(-1)^{n-1}}{\sqrt{n} \cdot 8^{n}} (x-2)^{3 n}=\sum \frac{(-1)^{n-1} \cdot(-2)^{3 n}}{\sqrt{n} \cdot 8^{n}} =\sum \frac{(-1)^{n-1}(-1)^{3n}(2)^{3 n}}{\sqrt{n} \cdot 8^{n}} \)

\( =\sum \frac{(-1)^{4 n-1}\ 8^n}{\sqrt{n}\ 8^4} \)but \( (-1)^{(4n-1)}=(-1)^{4 n} \cdot(-1)^{-1}=-(-1)^{4 n}=-1 \)

\( \sum \frac{(-1)^{4 n-1}}{\sqrt{n}}= -\sum \frac{1}{\sqrt{n}} \) whic is a Divergent p-serirs

when \( x=4 \Rightarrow \sum \frac{(-1)}{\sqrt{n} \cdot 8^{n}} \cdot(x-2)^{3 n}=\sum \frac{(-1)^{n-1}}{\sqrt{n} \cdot 8^{n}}(2)^{3 n}=\sum \frac{(-1)^{n-1} \cdot 8^{n}}{\sqrt{n} \cdot x^{n}} \)

\( =\sum \frac{(-1)^{n-1}}{\sqrt{n}} \) Alternating Series \( b_{n}=\frac{1}{\sqrt{n}} \rightarrow \sum |a_n| =\sum \frac{1}{\sqrt{n}} \)

is Divergent Cp-series and  \( p=\frac{1}{2}<1 ) \)

\( A \cdot S \cdot T : \)

 \( \lim _{n \rightarrow \infty} b_{n}=\lim _{n \rightarrow \infty} \frac{1}{\sqrt{n}}=\frac{1}{\infty}=0 \)

 \( f(x)=\frac{1}{\sqrt{x}} \rightarrow f^{\prime}(x)=\frac{-\frac{1}{2 \sqrt{x}}(1)}{(\sqrt{x})^{2}}=\frac{-\frac{1}{2 x^{1/2} }}{x^{1}}=\frac{-1}{2 x^{3 / 2}}<0 \)

\( \{b n\} \) is decreasing

\( \sum \frac{(-1)^{n-1}}{\sqrt{n}} \) is \(C.C\) by \(A.S.T\) \( , \sum \frac{(-1)^{n-1}}{\sqrt{n} \  8^{n}} (x-2)^{3 n} \) is \(C\)

at \(x=4\), The interval of Convergenc is \( (0,4] \)

Radius of Comergence \(=2\)

No comments yet

Join the conversation

Join Notatee Today!